Contextual Development: Situating the Social Change Model of Leadership Development Within a Broader Reality of Comprehensive Support. Issue 3 (2nd July 2016) - Whitten-Andrews, Jeanie
Abstract: The social change model has proven an effective and widely utilized model assisting college students in leadership development toward positive social change. However, while this particular model gives much needed attention to the process of development leading to social change, it fails to acknowledge the external factors which significantly affect the student's capacity to develop effectively. This article discusses these issues and proposes "comprehensive support" as an additional component of the model, including two additional "C's." This addition attempts to more fully acknowledge the external realities affecting the potential for effective student leadership among college students.